Analysis Of Educators' Role And Character In Children's Character Education Based On The Qur'an: A Qualitative Content Analysis - Azza Khumairah; Muhamad Yusuf; Oki Mitra (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study analyzes the role and character of educators in children's character education based on the Qur'an, focusing on Surah Luqman verses 13–17. Using a qualitative content analysis approach, the research explores the educational messages in the verses and their implications for addressing contemporary moral and spiritual development challenges. Primary data sources include the Qur'an and classical and modern tafsir works, supported by secondary references such as books, journals, and scholarly articles. The findings identify two core character values emphasized in the verses—religiosity and communicativeness—which are fundamental foundations for shaping children's ethical, social, and spiritual growth. The analysis further underscores the comprehensive role of parents and educators, encompassing knowledge preparation, compassionate nurturing, moral guidance, and effective communication that integrates firmness with empathy. Essential educator traits highlighted in the study include religiosity, patience, diligence, and communicative competence, central pillars of holistic character education. The study concludes that embedding these Qur'anic principles into educational practice provides a relevant and comprehensive framework for strengthening children's moral reasoning, spiritual awareness, and social responsibility, thereby offering solutions to the current decline in educational integrity and character values.